Klimatologische und vegetationskundliche Höhengradienten im Death Valley National Monument - Richter, Michael; Schröder, Rolf (ERDKUNDE, 1991)
The mountains framing the Death Valley-depression offer ideal opportunities for model-studies on climaticecological vertical gradients in arid zones, as this area represents an extreme desert with a great floristic potential. Four principles, which probably apply to altitude-changes in arid zones in general, are especially dominant. (1) Concerning microclimatic factors, the decrease of surface-temperature-amplitudes with increasing altitude means a contrast with characteristics of humid highlands. This is due to ground-humidity increasing with height, which causes the actual evaporation to rise, resulting in a growing amount of latent energy-transfer (decreasing Bowen-ratio). (2) Plant-adaptations show a virtually consistent appearance of the nanophyllia in low as well as in high elevations. This differs from the situation in humid mountains, where increasing radiation causes a considerable reduction of leafsize. (3) H, for the same reason, there is a relative increase of scleromorphous superseding mesomorphous tissue, the mesomorphous leaf-structures concentrate in higher altitudes of the Death Valley-region, due to the vertical humidity-increase. (4) The Merriam Effect, i. e. the depression of life zones caused by convectional rain increasing with the mountain mass, is another difference to semi- or perhumid ranges, where radiation-gain has an opposite effect.